2019
DOI: 10.1186/s12943-019-1006-2
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ-DONSON facilitates gastric cancer growth and invasion via NURF complex dependent activation of transcription factor SOX4

Abstract: Background Circular RNAs (circRNAs) are a novel type of noncoding RNAs and play important roles in tumorigenesis, including gastric cancer (GC). However, the functions of most circRNAs remain poorly understood. In our study, we aimed to investigate the functions of a new circRNA circ-DONSON in GC progression. Methods The expression of circ-DONSON in gastric cancer tissues and adjacent normal tissues was analyzed by bioinformatics method, qRT-PCR, Northern blotting and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
177
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(179 citation statements)
references
References 32 publications
2
177
0
Order By: Relevance
“…Recently, DONSON was found to encode a novel fork protein factor and play an important role in mammalian DNA replication and genome stability. Moreover, its mutation caused microcephalic dwarfism . Previous studies showed that DONSON is a member of replisome complex and protected stalled or damaged replication forks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, DONSON was found to encode a novel fork protein factor and play an important role in mammalian DNA replication and genome stability. Moreover, its mutation caused microcephalic dwarfism . Previous studies showed that DONSON is a member of replisome complex and protected stalled or damaged replication forks.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that expression of circular RNAs in cancer cells have participated in oncogenesis . Interestingly, overexpression of circ‐ DONSON (derived from exon 3 to exon 8 of DONSON mRNA) was detected in gastric cancer and its aberrant expression promoted gastric cancer cell aggressiveness through initiated SOX4 expression . The oncogenic roles of the circ‐ DONSON in ccRCC cells need to be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicated that circRNAs act as potential biomarkers in patients with GC. Upregulation of circ-DON-SON, circAKT3, and circDLST [8,11,13] or downregulation of KIAA1244, circPSMC3, and circFAT1(e2) [14][15][16] is regarded as independent prognostic factors of poor prognosis in patients with GC. Herein, we identified a novel circDUSP16, and it was resistant to RNase R and localized in the cytoplasm of GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Circular RNAa (circRNAs), a new subtype of ncRNAs, have covalently closed loop structures with a back splice site between 5′-and 3′-end and exhibit higher conservativity than the corresponding linear RNAs duo to resistance to RNase R [7]. Mounting data indicated that circRNAs act critical roles in multiple molecular mechanisms including tumor biomarkers, regulating gene expression, and sponging miRNAs in cancer [8][9][10]. Circ-DONSON [8], circAGO2 [9], circAKT3 [11], circNRIP1 [12], and circDLST [13] are upregulated in GC tissues samples, and their increased expression is associated with TNM stage and poor prognosis in patients with GC [8,11,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation